Use of failure mode and effect analysis to improve the monoclonal antibody drugs management process in pharmacy intravenous admixture services - Jian Cai; Min-Xian Li; Shuai Lu; Dan Shen; Wei Xie; Jian-Jun Zhu; Guo-Jun Jiang; Chun-Xiao Lu (Scientific Reports)
Abstract Monoclonal antibodies (mAbs) constitute a new form of immunotherapy that has shown great success in long-term tumour control. These injectable drugs are managed and compounded by the Pharmacy Intravenous Admixture Services (PIVAS) staff in a specified sterile environment. This study utilized failure mode and effect analysis (FMEA) as a risk management tool to manage mAb drugs within the PIVAS. The nine-member multidisciplinary team mapped the processes; evaluated the severity, occurrence, and detection of each subprocess; and calculated the risk priority number (RPN). Further corrective actions were taken for high-risk steps, followed by re-evaluation and scoring to achieve a low-risk process. We identified seven major processes and twenty-eight subprocesses involved in the management of mAb drugs in PIVAS. A total of thirteen high-risk failure modes with an assigned RPN 1 were selected. This selection represents the first calculated RPN values, resulting in a total score of 3375. After a first round of evaluation and implementation of corrective actions, the RPN 2 score decreased to 464. Following a second round of the FMEA process, the RPN 3 score was further reduced to 51. Through refinement, we successfully mitigated the occurrence of high-risk failure modes of mAb drugs in PIVAS. These efforts are aimed at enhancing the safety and efficacy of mAb drugs, ultimately ensuring patient safety.